2022
DOI: 10.22201/fca.24488410e.2022.2920
|View full text |Cite
|
Sign up to set email alerts
|

Are there “day-of-the-week” and “holiday” anomalies in the mexican stock market?

Abstract: Are there "day-of-the-week" and "holiday" anomalies in the mexican stock market?¿Hay anomalías "día de la semana" y "día festivo" en el mercado accionario mexicano?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Winkelried & Iberico (2018) found the DOW effect in five of the six Latin American stock markets they examined. Villarreal-Samaniego, Santillán-Salgado, & Lagunes-Pérez (2022) concluded that the DOW effect was consistently present in the Mexican stock market's returns and volatility.…”
Section: Introductionmentioning
confidence: 99%
“…Winkelried & Iberico (2018) found the DOW effect in five of the six Latin American stock markets they examined. Villarreal-Samaniego, Santillán-Salgado, & Lagunes-Pérez (2022) concluded that the DOW effect was consistently present in the Mexican stock market's returns and volatility.…”
Section: Introductionmentioning
confidence: 99%